A PARTICIPAÇÃO DA SOCIEDADE CIVIL NA GESTÃO DA SAÚDE PÚBLICA EM PONTA GROSSA - PR ATRAVÉS DO CONSELHO MUNICIPAL E CONSELHOS LOCAIS DE SAÚDE - Luiz, Isaias Cantoia (2007)
This study analyzes the participation of the society in the management of the public health from the creation of the Local Advice of Health, in the city of Ponta Grossa - Paraná after 2002. It investigates the process of rganization, the dynamics of functioning and which the strategies used for the effectuation of the Local Advice of Health, considered as a new space of negotiation between State and Society. The research procedures had constituted in literature revision on the thematic ones that they surround the research object, systematization about the politics of health in Brazil as determinative of the configurations of the municipal politics and inquiry of the local reality through documentary research and interviews with the significant citizens that had lived deeply the experience of implantation and development of the Local Advice of Health in Ponta Grossa.